Co-infection in pediatric pertussis during 2023 and 2024 in southern China: pathogen distribution characteristic and influence on manifestation of pertussis - Lai, Weiming; Guo, Junfei; Zhou, Xiaoying; Luo, Yasha; Zheng, Minling; Mai, Qiongdan; Xiong, Jiana; Luo, Mingyong (Frontiers in Microbiology, 2025)
ObjectiveWe sought to examine the pathogen composition of co-infections in pertussis during 2023 and 2024 and assess the impacts of co-infection on pertussis.MethodsClinical data of pediatric pertussis patients were retrospectively analyzed. The impact of co-infections on pertussis, the detection rate and composition of co-pathogens were analyzed. Culture, polymerase chain reaction, or metagenomic sequencing were used in pertussis or co-pathogens detection.ResultsAmong 620 pertussis patients, 110 patients co-infected with bacteria, 106 co-infected with virus, and 98 co-infected with both bacteria and virus. M. pneumoniae (114, 18.39%), M. catarrhalis (44, 7.1%), and H. influenzae (26, 4.19%) were the most common bacterial co-pathogens, and Rhinovirus (100, 16.12%), Cytomegalovirus (31, 5%), and Influenza virus A&B (28, 4.52%) were the most common viral co-pathogens. Patients with co-infections exhibited more severe manifestations than those with pertussis alone, and the severity was associated with the type and number of pathogens. The composition of co-pathogens linked to the age and hospitalization status of the patients. M. pneumoniae (91, 21.06%), M. catarrhalis (32, 7.41%), and Influenza virus A&B (22, 5.09%) primarily caused co-infections in older, non-hospitalized patients, whereas Cytomegalovirus [(19, 14.39%) non-ICU, (12, 21.43%) ICU] and Respiratory syncytial virus [(8, 6.06%) non-ICU, (8, 14.28%) ICU] were more common in younger, hospitalized patients.ConclusionCo-infections are common among pertussis and can intensify clinical symptoms. Distribution of co-infecting pathogens is associated with age and hospitalization status, and the impacts of co-infection on the manifestations of pertussis varied according to the types and number of co-pathogens.